A homozygous potentially pathogenic variant in the PAXBP1 gene in a large family with global developmental delay and myopathic hypotonia. Issue 6 (15th September 2017) - Alharby, E.; Albalawi, A.M.; Nasir, A.; Alhijji, S.A.; Mahmood, A.; Ramzan, K.; Abdusamad, F.; Aljohani, A.; Abdelsalam, O.; Eldardear, A.; Basit, S.
Abstract : PAX binding protein 1 ( PAXBP1 ) is an adaptor protein linking the transcription factor PAX3 and PAX7 to the histone methylation machinery. PAXBP1 is a nuclear protein and its high expression is known in brain cerebellar hemisphere and cerebellum. Moreover, it is also found in abundance in muscle precursor cells that are involved in myogenesis and skeletal muscles formation. Whole genome SNP genotyping and exome sequencing in a family with distinct syndrome of global developmental delay and hypotonia mapped the disease locus to the chromosome 21q22.11 and identified a homozygous missense variant (c.1612C>T) in the PAXBP1 gene, respectively. This variant is predicted to change the highly conserved strongly basic arginine at position 538 in the PAX7 binding domain of PAXBP1 to a neutral cysteine (p.Arg538Cys) residue. Arg538 is highly conserved and the variant is predicted to be deleterious by variety of in silico tools. Furthermore, protein modeling studies showed that in the mutant protein (Cys538), the shorter cysteine is incapable of forming hydrogen bond with the side chain of nearby Asp517 due to its reduced size and lower polarizability. As a consequence, a slight local perturbation of the loop conformation in the PAX7 binding domain of the PAXBP1 protein was observed. Our findings suggest that the pathogenic variant in PAX binding protein underlies distinct syndrome of global developmental delay and myopathic hypotonia. This clinical report should prompt a search for mutations in PAXBP1 in patients presenting with developmental delay and hypotonia. Moreover, these results imply that establishment of PAXBP1 targets and its spatiotemporal interaction will help in understanding of development of cerebellar and will provide basis for developing therapeutic approaches. Abstract :